Acute and delayed response to resistance exercise leading or not leading to muscle failure - Pareja‐Blanco, Fernando; Rodríguez‐Rosell, David; Sánchez‐Medina, Luis; Ribas‐Serna, Juan; López‐López, Covadonga; Mora‐Custodio, Ricardo; Yáñez‐García, Juan Manuel; González‐Badillo, Juan José (Clinical physiology and functional imaging, 2017)
Summary This study compared the time course of recovery following two resistance exercise protocols differing in the number of repetitions per set with regard to the maximum possible (to failure) number. Ten men performed three sets of 6 versus 12 repetitions with their 70% 1RM (3 × 6 [12] versus 3 × 12 [12]) in the bench press (BP) and squat (SQ) exercises. Mechanical [CMJ height, velocity against the 1 m s−1 load (V1‐load)], biochemical [testosterone, cortisol, growth hormone, prolactin, insulin‐like growth factor‐1, creatine kinase (CK)] and heart rate variability (HRV) and complexity (HRC) were assessed pre‐, postexercise (Post) and at 6, 24 and 48 h‐Post. Compared with 3 × 6 [12], the 3 × 12 [12] protocol resulted in significantly: higher repetition velocity loss within each set (BP: 65% versus 26%; SQ: 44% versus 20%); reduced V1‐load until 24 h‐Post (BP) and 6 h‐Post (SQ); decreased CMJ height up to 48 h‐Post; greater increases in cortisol (Post), prolactin (Post, 48 h‐Post) and CK (48 h‐Post); and reductions in HRV and HRC at Post. This study shows that the mechanical, neuroendocrine and autonomic cardiovascular response is markedly different when manipulating the number of repetitions per set. Halving the number of repetitions in relation to the maximum number that can be completed serves to minimize fatigue and speed up recovery following resistance training.